Association between antibiotic-immunotherapy exposure ratio and outcome in metastatic non small cell lung cancer. (June 2019) - Galli, Giulia; Triulzi, Tiziana; Proto, Claudia; Signorelli, Diego; Imbimbo, Martina; Poggi, Marta; Fucà, Giovanni; Ganzinelli, Monica; Vitali, Milena; Palmieri, Dario; Tessari, Anna; de Braud, Filippo; et al.
Highlights: Antibiotics induce imbalances in the composition of gut microbiota. Alterations of intestinal flora may impair the efficacy of immunotherapy (IO). We defined Antibiotic-IO Exposure Ratio (AIER) as "days of antibiotics /days of IO". NSCLC patients with an AIER higher than the median had a worse outcome during IO. The potential impact of AIER on the effects of IO deserves further investigation. Abstract: Objectives: Immunotherapy (IO) is effective in metastatic Non Small Cell Lung Cancer (NSCLC). Gut microbiota has an impact on immunity and its imbalance due to antibiotics may impair the efficacy of IO. We investigated this topic in a case series of NSCLC patients treated with IO. Materials and Methods: Data about all metastatic NSCLC patients treated with IO between 04/2013 and 01/2018 were collected. Patients were stratified according to antibiotic use during the Early IO Period (EIOP), and according to the Antibiotic-Immunotherapy Exposure Ratio (AIER) defined as "days of antibiotic/days of IO" during the Whole IO Period (WIOP). Survival was estimated using the Kaplan-Meier method. Log-rank test was used to compare the curves. Multivariate analyses were performed with the Cox model. Results: We analyzed 157 patients. Forty-six patients received antibiotics during the WIOP, 27 patients during the EIOP. No differences in either Progression-Free Survival (PFS) or Overall Survival (OS) were observed according to antibiotic use during the EIOP (p = 0.1772 and p = 0.2492, respectively). Considering the WIOP, median AIER was 4.2%. The patients with a higher AIER had worse PFS (p < 0.0001) and OS (p = 0.0004) than the others. Results were significant also after correction for the IO line (p = 0.0018 for PFS) and performance status (p < 0.0001 for PFS, p = 0.0052 for OS). Conclusion: Although no difference in outcome were observed with antibiotic use in the EIOP, a detrimental effect became evident for patients with a higher AIER in the WIOP. If its relevance is confirmed, AIER may become an innovative variable for estimating the impact of antibiotics on IO efficacy.